Factorization of a Matrix Differential Operator Using Functions in Its Kernel. Issue 7 (1st August 2016) - Kasman, Alex
Abstract: Just as knowing some roots of a polynomial allows one to factor it, a well-known result provides a factorization of any scalar differential operator given a set of linearly independent functions in its kernel. This note provides a straightforward generalization to the case of matrix coefficient differential operators.